Perceptions of Pre-Service Science Teachers in Nusantara Capital City About The Greenhouse Effect - Puardmi Damayanti; Shelly Efwinda; Muhammad Junus (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2023)
The Greenhouse Effect is essential in protecting the survival of living things on Earth. However, the system will crash if the Greenhouse Effect is excessive. The form of damage is global warming which can cause system changes to ecosystems on Earth. A group that can take a proactive role in this educational context is the student community. This study aims to provide an overview of preservice science teachers' perception of the Greenhouse Effect and understanding of the environment, especially in the Nusantara capital city. The research method used an exploratory study with a quantitative and qualitative approach. The data collection technique used a survey using a questionnaire instrument to students of Physics, Biology, Chemistry, and Geography Education at Mulawarman University. The questionnaire in this study used was developed by Boyes and Stanisstret (1993). The questionnaire consisted of 36 statements rated on a 3-point Likert scale. The statement was divided into three sections, each containing 12 statements, distributed using Google Forms. The results showed that preservice science teachers had many misperceptions and were still wrong in determining the cause-and-effect relationship of the greenhouse effect and solutions to reduce it.